Multi-Tensor Investigation of Orbitofrontal Cortex Tracts Affected in Subcaudate Tractotomy - Yang, Jimmy C. (Brain Imaging Behav, 2015)
Subcaudate tractotomy (SCT) is a neurosurgical lesioning procedure that can reduce symptoms in medically intractable obsessive compulsive disorder (OCD). Due to the putative importance the orbitofrontal cortex (OFC) in symptomatology, fibers that connect the OFC, SCT lesion, and either the thalamus or brainstem were investigated with two-tensor tractography using an unscented Kalman filter approach. From this dataset, fibers were warped to Montreal Neurological Institute space, and probability maps with center-of-mass analysis were subsequently generated. In comparing fibers from the same OFC region, including medial OFC (mOFC), central OFC (cOFC), and lateral OFC (lOFC), the area of divergence for fibers connected with the thalamus versus the brainstem is posterior to the anterior commissure. At the anterior commissure, fibers connected with the thalamus run dorsal to those connected with the brainstem. As OFC fibers travel through the ventral aspect of the internal capsule, lOFC fibers are dorsal to cOFC and mOFC fibers. Using neuroanatomical comparison, tracts coursing between the OFC and thalamus are likely part of the anterior thalamic radiations, while those between the OFC and brainstem likely belong to the medial forebrain bundle. These data support the involvement of the OFC in OCD and may be relevant to creating differential lesional procedures of specific tracts or to developing deep brain stimulation programming paradigms.